Hubungan Kompetensi Komunikasi Interpersonal dengan Self-Efficacy Mahasiswa Fikom Unisba 2017 - Andre Tadya Fahlevi; Anne Maryani (Jurnal Riset Manajemen Komunikasi, 2022)
Abstract. This theme was chosen because the researcher saw that in carrying out their duties, final year students of Communication Science needed interpersonal communication competence in fulfilling their needs. Understanding some aspects is very necessary, because communication cannot be done arbitrarily and some of them become a support for interpersonal communication in achieving its goals. Because the selected sample is 2017/final level students, interests that require interpersonal communication competence include working on a thesis. Quantitative is the approach used in this research. Data collection tools in the form of a questionnaire questionnaire of interpersonal communication competence with self efficacy. The questions compiled by the researchers were then distributed to the respondents who were taken by random sampling technique. From a total of 171 students who have signed a thesis, 52 samples are taken randomly with the limitation of respondents having to be listed in the database and being in the Class of 2017. The scores collected are entered into the Coding Sheet. Data analysis used is Pearson Product Moment with SPSS program. The result of this study is that there is a significant relationship between the communication motivation variable and self-efficacy with an rtable value of 0.238. Second, there is a significant relationship between the variable knowledge of communication and self-efficacy with an rtable value of 0.582 Abstrak. Tema ini dipilih karena peneliti melihat dalam melaksanakan tugasnya, mahasiswa tingkat akhir Ilmu Komunikasi membutuhkan kompetensi komunikasi interpersonal dalam pemenuhan kebutuhannya . Pemahaman beberapa aspek sangat perlu, berhubung dengan komunikasi tidak dapat dilakukan secara sembarang dan diantaranya menjadi penunjang komunikasi interpersonal dalam mencapai tujuannya. Karena sampel yang dipilih adalah mahasiswa angkatan 2017/tingkat akhir, kepentingan yang membutuhkan kompetensi komunikasi interpersonal diantaranya mengerjakan skripsi. Kuantitatif menjadi pendekatan yang digunakan penelitian ini. Alat pengumpulan data berupa angket kuesioner kompetensi komunikasi interpersonal dengan self efficacy. Pertanyaan yang disusun oleh peneliti selanjutnya disebar pada responden yang diambil dengan teknik random sampling. Dari jumlah total 171 mahasiswa yang telah mengontrak skripsi diambil 52 sampel secara acak dengan batasan responden harus tertera di dalam database dan berada diAngkatan 2017. Skor yang terkumpul dimasukan ke dalam Coding Sheet. Analisis data yang digunakan adalah Pearson Product Moment dengan program SPSS. Hasil penelitian ini ialah terdapat hubungan signifikan antara variabel motivasi komunikasi dengan efikasi diri dengan nilai rtabel yaitu 0,238. Yang kedua, terdapat hubungan signifikan antara variabel pengetahuan komunikasi dengan efikasi diri dengan nilai rtabel yaitu 0,582.